2013
DOI: 10.1152/jn.00751.2012
|View full text |Cite
|
Sign up to set email alerts
|

Control of position and movement is simplified by combined muscle spindle and Golgi tendon organ feedback

Abstract: Kistemaker DA, Van Soest AJ, Wong JD, Kurtzer I, Gribble PL. Control of position and movement is simplified by combined muscle spindle and Golgi tendon organ feedback. J Neurophysiol 109: 1126-1139, 2013. First published October 24, 2012 doi:10.1152/jn.00751.2012.-Whereas muscle spindles play a prominent role in current theories of human motor control, Golgi tendon organs (GTO) and their associated tendons are often neglected. This is surprising since there is ample evidence that both tendons and GTOs contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 112 publications
(129 reference statements)
5
68
0
2
Order By: Relevance
“…However, the muscle spindle contained in the lumbricals may sense the state of tension in each of the tendinous slips of the FHL and the tendon of the FDL, as well as that in the tendon of the extensor muscle during movements of the foot. Several theories of motor control propose that muscle spindle information is used by the central nervous system to generate muscle activation patterns in a predictive manner [6,22,23]. Therefore, it is thought that at first the lumbricals may sense the tension in the tendons of the flexors and extensors, and using this information they may assist flexion and extension of the toes for following coordinated movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the muscle spindle contained in the lumbricals may sense the state of tension in each of the tendinous slips of the FHL and the tendon of the FDL, as well as that in the tendon of the extensor muscle during movements of the foot. Several theories of motor control propose that muscle spindle information is used by the central nervous system to generate muscle activation patterns in a predictive manner [6,22,23]. Therefore, it is thought that at first the lumbricals may sense the tension in the tendons of the flexors and extensors, and using this information they may assist flexion and extension of the toes for following coordinated movements.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle spindles provide information related to the length and contraction velocity of the muscle fibers [6,19], and proprioceptive sensation provides information as to the degree of contraction of the muscle and the state of tension in the tendon. This information is essential for the coordination of movement [25], and it has been suggested that the sensory function of the lumbricals in the hand is more important than its motor function.…”
Section: Introductionmentioning
confidence: 99%
“…2. Golgi tendon organs (GTO) are located at the conjunction between muscle and tendon and can be modeled as force transducers used by the CNS [40]. It is possible that their position at the interface provides a linear relationship with maximum sensitivity between the force transmitted and elongation of the tendon, therefore providing positional information for the controlled variable z(t) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Golgi tendon organs (GTO) are located at the conjunction between muscle and tendon and can be modeled as force transducers used by the CNS [40]. It is possible that their position at the interface provides a linear relationship with maximum sensitivity between the force transmitted and elongation of the tendon, therefore providing positional information for the controlled variable z(t) [40]. In robotics, the indirect force control of a system presents a compliant element (tendon) acting as stabilizing impedance buffers between the force-generating element (muscle) and the environment, is referred to as serial elastic control [41].…”
Section: Discussionmentioning
confidence: 99%
“…Watson and S. Nayak tendon reflex (Kistemaker et al 2013), physiologic tremor and mechanical properties of the body (Hallett 1998), and "limb resonance" (Lakie et al 2012). Hallett states in "Overview of Human Tremor Physiology" (1998) that: "physiologic tremor is a ubiquitous normal phenomenon."…”
mentioning
confidence: 99%